MTN-017: A Rectal Phase 2 Extended Safety and Acceptability Study of Tenofovir Reduced-Glycerin 1% Gel - Cranston, Ross D. (Clin Infect Dis, 2017)
BACKGROUND. Human immunodeficiency virus (HIV) disproportionately affects men who have sex with men (MSM) and transgender women (TGW). Safe and acceptable topical HIV prevention methods that target the rectum are needed. METHODS. MTN-017 was a phase 2, 3-period, randomized sequence, open-label, expanded safety and acceptability crossover study comparing rectally applied reduced-glycerin (RG) 1% tenofovir (TFV) and oral emtricitabine/TFV disoproxil fumarate (FTC/TDF). In each 8-week study period participants were randomized to RG-TFV rectal gel daily, or RG-TFV rectal gel before and after receptive anal intercourse (RAI; or at least twice weekly in the event of no RAI), or daily oral FTC/TDF. RESULTS. MSM and TGW (n = 195) were enrolled from 8 sites in the United States, Thailand, Peru, and South Africa with mean age of 31.1 years (range 18-64). There were no differences in ≥grade 2 adverse event rates between daily gel (incidence rate ratio [IRR], 1.09; P = .59) or RAI gel (IRR, 0.90; P = .51) compared to FTC/TDF. High adherence (≥80% of prescribed doses assessed by unused product return and Short Message System reports) was less likely in the daily gel regimen (odds ratio [OR], 0.35; P < .001), and participants reported less likelihood of future daily gel use for HIV protection compared to FTC/TDF (OR, 0.38; P < .001). CONCLUSIONS. Rectal application of RG TFV gel was safe in MSM and TGW. Adherence and product use likelihood were similar for the intermittent gel and daily oral FTC/TDF regimens, but lower for the daily gel regimen. CLINICAL TRIALS REGISTRATION: NCT01687218.